Recovering the TV career of Korean American comedian Johnny Yune. Issue 4 (1st October 2020) - Jung, Grace
ABSTRACT: This article examines the late Korean American stand-up comedian Johnny Yune's television career at NBC. Yune made his comedy debut on The Tonight Show starring Johnny Carson in 1978 and charmed the nation's most beloved talk show host of that era. As a result, NBC signed Yune as the lead in three pilots over the next two years but his career on network television abruptly ended in 1980. Some of the factors that contributed to this end include the mystification of South Korea(ns) as a nation and identity, NBC's struggle to compete against ABC and CBS, and systemic racism in the US. Yune's stand-up routine was rooted in racialized and politicized self-deprecation which appealed to the dominant biases of mainstream (white) Americans in the late 1970s. With that said, given America's hazy recollection of its involvement in the Korean War (1950–1953), Yune's comedic material produced a memory in place of its forgottenness. This paper historicizes Yune's transnational career as an actor, comedian, filmmaker, and talk show host in Los Angeles and Seoul, as well as his reception in America, which was impacted by the 'cold' war between the US and USSR.